Enhancing ADR through Collaborative Clinical Legal Education: Law Schools and BANI's Optimized Partnership in Indonesia - Herliana Herliana; Umar Mubdi; Arief Sempurno; Erma Nuzulia Syifa (Universitas Negeri Semarang, 2023)
This article endeavors to seamlessly incorporate the teaching of Alternative Dispute Resolution (ADR) directly into the framework of Clinical Legal Education (CLE), utilizing collaboration with esteemed dispute settlement institutions, notably the Indonesian Arbitration Center (BANI) and the Indonesian National Mediation Center (PMN). The imperative for such integration is underscored by the heightened demand for skilled arbitrators and mediators, given the ubiquitous inclusion of ADR clauses in nearly every contractual arrangement. In the contemporary legal landscape where ADR clauses have become standard practice for resolving disputes arising from contractual relationships, the professional roles of arbitrators and mediators are indispensable. The significance of this initiative lies in recognizing that the success of CLE in ADR in Indonesia necessitates a fundamental shift in the mindset of the legal community. It is asserted that the conventional teaching methods, traditionally confined to the classroom, are insufficient for the cultivation of skills pertinent to amicable dispute resolution. Thus, the article advocates for the active involvement of professional arbitrators and mediators, calling for their comprehensive integration and support not only within law school curricula but also in the broader community. This transformative approach aims to bridge the practical gap between theoretical instruction and real-world application, envisioning a legal education system that produces professionals adept at ethical and effective dispute resolution in Indonesia.